Spatial Distribution of Major Fish Species Catches and Their Relationship with Environmental Factors in the Beibu Gulf, South China Sea - Menghui Li; Xuehui Wang; Feiyan Du; Shuai Peng; Lianggen Wang; Dianrong Sun; Yuezhong Wang; Pimao Chen; Yongsong Qiu (Fishes, 2023)
This study focused on major fish species caught from different ecological habitats to analyze the habitat changes in economically important fish in the Beibu Gulf. The maximum entropy model was constructed based on the data from 26 voyages obtained through the otter trawl fishery stock surveys conducted in the Beibu Gulf from 2006 to 2018. A total of 10 taxa of major fish catches, belonging to 4 families, 1 genus, and 5 species, were analyzed for their distribution characteristics in potential habitats during various ecological periods, specifically the withered and high-water periods, as well as their relationships with crucial environmental factors. During both the withered and high-water periods, the average area under the curve was 0.927, and all models had values exceeding 0.9. Salinity was identified as the principal factor during both periods. The salinity niche of Acropoma japonicum and the primary productivity niche of Sciaenidae were identified as the most restricted factors. The total distribution area of potentially suitable regions for major fish catches extended between 106°30′–109°45′ E and 17°30′–20°45′ N, and the area was lesser during the withered period. During the withered period, the distribution areas of Sciaenidae, Leiognathidae, and Saurida increased, while the distribution area of Trachurus japonicus increased during the high-water period. Sciaenidae and Trachurus japonicus exhibited the highest rates of change at 6.22% and 10.92%, respectively. This indicates that the high-water period may expand the range of suitable habitats for large catches that have an ideal habitat status in the Beibu Gulf. Therefore, it is crucial to anticipate the potential fish habitats in the Beibu Gulf and clarify their spatial distribution patterns.